The Importance of Culture in Addressing Domestic Violence for First Nation's Women - Klingspohn, Donna M. (Frontiers in Psychology, 2018)
Indigenous women in Canada face a range of health and social issues including domestic violence. Indigenous women (First Nations, Inuit and Métis) are six times more likely to be killed than non-Aboriginal women. (Miladnovic and Mulligan 2015) (Homicide in Canada, 2014) Aboriginal women are 2.5 times more likely to be victims of violence than non-Aboriginal women. (Robertson, 2010). These and other statistics highlight a significant difference in the level of violence experienced by Indigenous women to that experienced by women in the mainstream population in Canada. The historical impacts of colonization and forced assimilation of aboriginal people in Canada are viewed as the main social determinant of health for aboriginal people in Canada, as they led to intergenerational trauma, with communities struggling today against discrimination, stigma, poverty and social exclusion. Most disturbing and damaging are the outcomes of domestic violence, mental health and addiction issues. (Prussing, 2014) First Nation’s women who want to leave a violent situation have limited access to helping services, as most are located in large cities and towns, far from remote reserves where many of the women live. Services were originally designed by and for the mainstream population. First Nation’s women who manage to access these programs often find staff with limited cultural competence and program supports that have little cultural safety or relevance for them. Indigenous culture is defined in various levels of legislation as having a set of specific rights based on their historical ties to a particular region, with cultural or historical distinctiveness from the mainstream and other populations. (Indigenous Peoples at the UN (2014). In Canada, indigenous cultural beliefs are closely tied to belief in a creator, ancestors and the natural world, influencing their spirituality and their political perspectives. (Waldram, et al, 2006). Cultural safety, a concept that emerged in the 1980’s in New Zealand, is viewed as an environment that is spiritually, socially, emotionally and physically safe for people; where cultural identity is recognized and valued through shared respect, meaning, knowledge and the experience of learning together. This paper will explore current evidence-based literature to determine if there is empirical evidence